7 - Higher Education as an African Public Sphere and the University as a Site of Resistance and Claim of Ownership for the National Project - Assié-Lumumba N’Dri T. (Africa Development, 2021)
Throughout the African continent, albeit a product of imperial domination, every state at independence conceived a national project, which aimed at building a nation-state with a clearly articulated development agenda. Education as a social institution was considered requisite toward the actualisation of the national project. The sub-sector of higher education, and particularly the university, appeared as an indispensable agency. Given the general colonial policy of exclusion of Africans from university education, the right of African states to build their national/public universities epitomised self-determination at independence. The independence movements in the 1950s-1960s coincided also with the regained popularity of human capital theory that stipulated that education, especially the highest levels, constituted an investment for individual socio-economic attainment and social mobility as well as national and structural development. From its inception, the Western style of university that was conceived out of the colonial experience represented a special site for contention and affirmation of the Africans to realize their national projects. In the context of globalisation, international organisations and programmes such as the World Bank and General Agreement on Trade in Services (GATS) have emerged as proxies of the old colonial powers with the same goal of influencing the policies that restrict or shape higher education in African countries. Key constituencies of African universities, namely students and teaching staff, have resisted such infringement on Africans’ rights to university education and autonomy in determining their domestic policies. The main objective of this article is to analyse the evolution of the African university as a site for the continued struggle for self-determination. It will be argued that, in spite of the history of a few institutions in a handful of countries, the African university in the 21st Century re- flects essentially the colonial relations. Thus, for instance, the new Infor- mation and Communication Technologies (ICTs) and distance learning programmes, and the emerging private universities in the context of liber- alisation mantra, will also be analysed in the framework of the liberalisa- tion policies that have been promoted by the global colonial proxies. In this article, the public mission of the university, be it public or private, will be examined. The approach will be basically historical, assessing the actors and their transformations and mutations within the same reality of the structural inequality of power in the global system and various Afri- can responses through continued resistance and affirmation. It will ad- dress the fundamental question of the search for the public university or the university with a public mission for the production of relevant knowl- edge in the various disciplines, critical thinking and new paradigms, and methodologies to promote social progress amidst the challenges of the dominant liberal globalisation and the objective conditions of the African States, societies, and people.